Development of FTO inverse opal structural-based photoanodes for photoelectrochemical water splitting applications - Ng, Shi Yun (2019)
To sustain the increasing demand for energy, solar energy has been identified as a great renewable and clean energy source. However, since solar energy is inconsistent due to geological differences, photoelectrochemical (PEC) water splitting were introduced to split water molecules into hydrogen and oxygen via the absorption of sunlight, where the former is stored as chemical fuels that can be transported or used upon demand. In this study, to improve the PEC efficiencies, Fluorinated Tin Oxide inverse opal (FTO-IO) structures were used as the three-dimensional conductive skeleton for the loading of secondary materials. FTO-IO structural-based photoanodes were fabricated in this study with Cadmium Sulfide (CdS) nanorods and Zinc Indium Sulfide (ZIS) nanosheets deposited onto the conductive backbone respectively. The PEC performances of these photoanodes were measured with a three-electrode system and the results obtained were compared against photoanodes that were synthesised on FTO substrate using the same secondary materials. At a potential of 0.8 V versus Reversible Hydrogen Electrode (RHE), photocurrent densities of FTO-IO/CdS-NR shot up from 0 mA/cm2 to 5.9 mA/cm2 and FTO-IO/ZIS-NS yielded an increment of 0.25 mA/cm2 to 1.15 mA/cm2 under AM 1.5 G light illumination. Both photocurrents showed tremendous improvement as compared to those achieved with FTO glass, which was around three and five times higher respectively. These enhancements can be attributed to the excellent charge collection ability and multiple light scattering of FTO-IO structure. To achieve better PEC efficiencies, other works such as heterojunction engineering can be performed.